Opposing Roles of the Staphylococcus aureus Virulence Regulators, Agr and Sar, in Triton X-100- and Penicillin-Induced Autolysis - Fujimoto, David F. (American Society for Microbiology, 1998)
The regulation of murein hydrolases is a critical aspect of peptidoglycan growth and metabolism. In the present study, we demonstrate that mutations within the Staphylococcus aureus virulence factor regulatory genes, agr and sar, affect autolysis, resulting in decreased and increased autolysis rates, respectively. Zymographic analyses of these mutant strains suggest that agr and sar exert their effects on autolysis, in part, by modulating murein hydrolase expression and/or activity.